Evaluation of the Buttress System of a Great Ottoman Mosque Against Gravity Loads and Horizontal Seismic Forces: The Case of the Istanbul Süleymaniye Mosque - Izol, Rabia; Gurel, Muhammet Arif; Mollamahmutoglu, Cagri; Avcil, Fatih (MDPI, 2025)
Historical mosques are some of the most valuable structures in Islamic societies. It is of primary importance to protect these structures and ensure their safe transmission to future generations. This study investigates the adequacy of the buttress system of the S & uuml;leymaniye Mosque in Istanbul, regarded as the 'symbol structure of Ottoman Architecture', against gravity and horizontal earthquake loads. Although several structural studies have been conducted on this unique building, the absence of any research on the buttress system, which clearly plays a significant role in its survival through many earthquakes, served as the main motivation for this study. After presenting the material properties, a finite element model of the structure was created. Finite element models were also developed for two hypothetical scenarios in which the outer depths of the buttresses were reduced by fifty percent or eliminated. The models and all analyses were performed using ABAQUS software. Gravity load analyses indicated that the mosque does not face any issues related to stresses or displacements. Nonlinear static analyses revealed that, with the current buttress dimensions, the structure can resist horizontal loads up to about 70% of self-weight along the Qibla axis and about 90% along the axis perpendicular to the Qibla. These findings are some of the most significant results obtained thus far in studies investigating the horizontal earthquake resistance of the mosque. Through performance analyses, it was determined that the structure can meet the limited damage performance criterion only with the current buttress depths; however, it cannot satisfy this performance level with reduced buttress dimensions. In conclusion, the study demonstrated that the buttress system of the S & uuml;leymaniye Mosque is highly effective against gravity loads and transverse seismic forces and that it was designed not only with practical experience but also with a solid understanding of structural behavior.
Keywords: S & uuml; leymaniye Mosque; buttress system; nonlinear static analysis; performance analysis; ABAQUS; MASONRY BUTTRESSES; VULNERABILITY; Construction & Building Technology; Engineering